Regulation, taxation, and resources: unpacking greenhouse gas emission drivers across G7 economies - Hossain, Mohammad Imtiaz; Ahmed, Md Emon; Islam, Mohammad Fakhrul; Alam, Md Karimul; Al Mamun, Mohammad Abdullah; Kazi, Md Tarique (John Wiley and Sons, 2026)
Advanced economies are under growing pressure to downscale greenhouse gas (GHG) emissions without undermining growth, yet G7 (Group of Seven) nations, representing almost 10% of the world's population, still generate one quarter of global GHGs. We have investigated the G7's GHG emission problem from 2000 to 2020, by integrating macroeconomic and environmental panel data to determine how stricter environmental policies, higher green tax revenue, resource dependency, trade openness, and globalization can reduce the G7's emission problem. We applied second-generation panel estimators alongside a state-of-the-art quantile-based robust model, called the method of moment quantile regression (MMQR), and employed a two-step generalized method of moments (GMM) to address the endogeneity concern. In doing so, we found the following three findings. First, tougher regulations and higher environmental tax yields are consistently associated with reducing the GHG emissions, with the effect intensifying in all regimes. Second, resource dependence remains a stubborn emission amplifier across the entire distribution. Third, the role of trade and globalization is minimal, sometimes insignificant, referring to the fact that the policy and structural factors dominate trade and integration effects. Policy pathways for the G7 thus focus on (i) synchronizing environmental policy stringency targets to strict carbon-pricing floors, (ii) recycling environmental tax revenue and implementing green globalization with cross-border trade to accelerate clean-tech diffusion, and (iii) deploying resource diversification to neutralize resource rent-driven lock-ins. Our policy mix can help wealthy, integrated economies translate fiscal and regulatory leverage into a rapid and equitable solution to reduce GHG emissions.